Liquid composition
Patent Information
- Application Number
- JP2024117710
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-15
- Filing Date
- 2024-07-23
- Publication Date
- 2025-02-28
AI Technical Summary
【0006】 本発明によれば、テトラフルオロエチレン系ポリマーと所定の無機フィラーとを含み、分散性に優れた組成物が提供される。かかる組成物からは、緻密で無機フィラーの偏在がなく、機械的特性、耐熱性に優れ、線膨張係数、誘電率及び誘電正接が低く、電気絶縁性を維持しつつ熱伝導性に優れ表面粗さが小さいシート等の成形物を形成でき、放熱材料として好適に使用できる。
Abstract
Description
[Technical field]
[0001] The present invention relates to a liquid composition containing a tetrafluoroethylene-based polymer and a specified filler. [Background technology]
[0002] In recent years, in order to cope with the increasing speed and frequency of mobile communication devices such as mobile phones, materials with low dielectric constant and low dielectric loss tangent are required for the insulating layer of the printed circuit board of the communication device, and tetrafluoroethylene-based polymers have attracted attention. As a material for forming an insulating layer containing such a polymer, a dispersion containing particles of a tetrafluoroethylene-based polymer and a liquid dispersion medium is known. Among them, aqueous dispersions have high versatility in the equipment required for their use and high selectivity for substrates to be coated, and various additives are being investigated to improve the liquid properties. Patent Document 1 proposes an aqueous dispersion in which an aqueous dispersion of fluororesin microparticles and an aluminum oxide microparticle sol are mixed together, so that both are suspended and dispersed together, and the aqueous dispersion can be stably maintained for three days or more. It is said that this aqueous dispersion can improve the heat resistance of the fluororesin and suppress thermal degradation. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-110220 A Summary of the Invention [Problem to be solved by the invention]
[0004] On the other hand, thermal interface materials (hereinafter also referred to as "TIM") are used as heat dissipation materials to dissipate large amounts of heat generated from electronic components such as computer chips (CPUs), video graphics arrays, servers, game consoles, smartphones, LED boards, and semiconductor modules including power semiconductors used in inverters and converters in electric vehicles and power transmission systems. TIMs typically have the role of transferring excess heat from electronic components to a heat diffusion section, and then transferring the heat to a heat sink. Conventionally, phase change materials such as paraffin wax, grease-like materials, and elastomeric tapes have been used as TIMs because they can spread in a very thin layer and provide intimate contact between adjacent surfaces. However, these materials have problems such as poor heat resistance (thermal stability) and are prone to performance degradation. In order to improve the thermal conductivity of resin materials and obtain heat dissipation materials applicable to TIMs, various methods of blending thermally conductive fillers into resins have been investigated. However, tetrafluoroethylene-based polymers have low affinity with other components. In addition, when a filler is added to an aqueous dispersion containing tetrafluoroethylene-based polymer particles in order to apply the aqueous dispersion to the heat dissipation material field, the inorganic fillers tend to aggregate with each other in the composition, which tends to reduce the mechanical properties of the molded product obtained therefrom. Furthermore, when an inorganic filler with a high specific gravity is mixed at a high concentration, the inorganic filler tends to settle in the composition, and also tends to settle in the coating layer. Therefore, there was a problem that the filler tends to be unevenly distributed in the molded product formed by baking the coating layer, making it difficult to fully exhibit thermal conductivity. The present inventors have discovered that an aqueous liquid composition containing particles of a tetrafluoroethylene-based polymer, a specified inorganic filler, and a specific water-soluble polymer, and having a specified thixotropic ratio, has excellent dispersibility, and that molded articles formed from it are dense with no uneven distribution of the inorganic filler, have excellent mechanical properties and heat resistance, a low linear expansion coefficient, a low dielectric constant and a low dielectric tangent, excellent thermal conductivity while maintaining electrical insulation, and can have reduced surface roughness, thereby completing the present invention. It is an object of the present invention to provide such a composition, and a heat dissipating material containing said composition. [Means for solving the problem]
[0005] The present invention has the following aspects. [1] A liquid composition comprising particles of a tetrafluoroethylene-based polymer, an inorganic filler having an average particle size of more than 10 μm and a specific gravity of 2 or more, a water-soluble polymer having a weight-average molecular weight of 200,000 or more, and water, and having a thixotropy ratio of 3 to 15. [2] The liquid composition according to [1], wherein the ratio of the average particle size of the inorganic filler to the average particle size of the tetrafluoroethylene-based polymer particles is 5 or more. [3] The liquid composition according to [1] or [2], wherein the average particle size of the particles of the tetrafluoroethylene polymer is 0.1 to 25 μm. [4] The specific surface area of the particles of the tetrafluoroethylene-based polymer is 6 m 2 The liquid composition according to any one of [1] to [3], wherein the liquid composition has a viscosity of more than 1000 s / g. [5] The liquid composition according to any one of [1] to [4], wherein the tetrafluoroethylene-based polymer is a heat-fusible tetrafluoroethylene-based polymer having an oxygen-containing polar group. [6] The liquid composition according to any one of [1] to [5], wherein the inorganic filler has an average particle size of more than 10 μm and not more than 100 μm. [7] The liquid composition according to any one of [1] to [6], wherein the inorganic filler is a metal or a metal oxide. [8] The liquid composition according to any one of [1] to [7], wherein the content of the tetrafluoroethylene-based polymer particles is 10 to 30 volume % and the content of the inorganic filler is 50 to 80 volume % based on the total amount of the tetrafluoroethylene-based polymer particles and the inorganic filler. [9] The liquid composition according to any one of [1] to [8], wherein the water-soluble polymer has a weight average molecular weight of 1,000,000 or more.
[10] The liquid composition according to any one of [1] to [9], wherein the water-soluble polymer is at least one selected from the group consisting of acrylic acid-based polymers, vinyl alcohol-based polymers, and cellulose-based polymers.
[11] The liquid composition according to any one of [1] to
[10] , wherein the content of the water-soluble polymer relative to the amount of the tetrafluoroethylene polymer particles is 0.1 to 1.0% by mass.
[12] A heat dissipating material containing the liquid composition according to any one of [1] to
[11] .
[13] A method for producing a molded article, comprising extruding the liquid composition according to any one of [1] to
[12] or disposing it on a surface of a substrate to obtain a molded article containing the tetrafluoroethylene-based polymer and the inorganic filler.
[14] A molded article comprising particles of a tetrafluoroethylene polymer and an inorganic filler having an average particle size exceeding 10 μm and a specific gravity of 3 or more, the molded article having a surface roughness Rz of 25 μm or less and a thermal conductivity of 5 W / m·K or more.
[15] A molded article according to
[14] having a thickness of 100 μm or more. Effect of the Invention
[0006] According to the present invention, a composition containing a tetrafluoroethylene-based polymer and a specific inorganic filler and having excellent dispersibility is provided. From such a composition, a molded product such as a sheet can be formed which is dense, does not have uneven distribution of the inorganic filler, has excellent mechanical properties and heat resistance, has a low linear expansion coefficient, a low dielectric constant and a low dielectric tangent, has excellent thermal conductivity while maintaining electrical insulation, and has small surface roughness, and can be suitably used as a heat dissipation material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The following terms have the following meanings. "Average particle size (D50)" is the cumulative 50% volumetric diameter of a particle or filler determined by a laser diffraction / scattering method. In other words, the particle size distribution is measured by a laser diffraction / scattering method, the total volume of the particle or filler group is set as 100%, a cumulative curve is calculated, and the particle size is the point on the cumulative curve where the cumulative volume is 50%. The D50 of particles or fillers is determined by dispersing the particles or fillers in water and analyzing them by a laser diffraction / scattering method using a laser diffraction / scattering type particle size distribution measuring device (LA-920 measuring device, manufactured by Horiba, Ltd.). The "specific surface area" of a particle is a value calculated by measuring the particle by a gas adsorption (constant volume method) BET multipoint method, and is determined using a BET specific surface area measurement device (for example, NOVA4200e (manufactured by Quantachrome Instruments)). "Melting temperature" is the temperature corresponding to the maximum of the melting peak of a polymer as measured by differential scanning calorimetry (DSC). The "glass transition temperature (Tg)" is a value measured by analyzing a polymer using the dynamic mechanical analysis (DMA) method. The "viscosity" is determined by measuring the composition using an E-type viscometer at 25° C. and a shear rate of 10 / sec. The measurement is repeated three times, and the average value of the three measurements is calculated. The "thixotropy ratio" is a value calculated by dividing the viscosity η1 of a composition measured at a shear rate of 10 / sec by the viscosity η2 measured at a shear rate of 100 / sec. The term "unit" in a polymer means an atomic group based on a monomer formed by polymerization of the monomer. The unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by processing the polymer. Hereinafter, a unit based on monomer a is also referred to simply as a "monomer a unit."
[0008] The liquid composition of the present invention (hereinafter also referred to as "the composition") contains particles (hereinafter also referred to as "F particles") of a tetrafluoroethylene polymer (hereinafter also referred to as "F polymer"), an inorganic filler having an average particle size of more than 10 μm and a specific gravity of 2 or more (hereinafter also referred to as "the inorganic filler"), a water-soluble polymer having a weight-average molecular weight of 200,000 or more, and water, and has a thixotropic ratio of 3 to 15.
[0009] The composition of the present invention has excellent dispersibility even when it contains the inorganic filler, and the inorganic filler is not unevenly distributed, so that it is easy to form a dense and highly uniform molded product such as a sheet. The reason for this is not necessarily clear, but is thought to be as follows. When a water-soluble polymer is added to an aqueous dispersion containing F particles, the viscosity of the aqueous dispersion can be increased, and the liquid properties such as thixotropy (thixotropy) can be improved. In the present composition, the polymer is a water-soluble polymer having a specific molecular weight or more, which develops in a matrix-like manner in water, promoting gentle interactions between the F particles and the present inorganic filler, and is thought to suppress the settling of the present inorganic filler while balancing the suppression of aggregation of the F particles and the present inorganic filler with the dispersion stability. In addition, in a molded product such as a sheet formed from the composition, the F particles and the inorganic filler are densely packed, and a high level of filler path is easily formed. In other words, it is considered that the water-soluble polymer promotes dense packing of the F polymer between the inorganic filler when a processed product such as a coating film is formed from the composition. It is considered that this improves the thermal conductivity of the molded product while maintaining the heat resistance, linear expansion coefficient, and electrical properties, especially electrical insulation. Therefore, it is believed that a molded article formed from this composition has high physical properties of the F polymer and the inorganic filler, is dense with no uneven distribution of the inorganic filler, has excellent mechanical properties and heat resistance, has a low linear expansion coefficient, dielectric constant and dielectric tangent, and has excellent thermal conductivity while maintaining electrical insulation. This tendency becomes more pronounced when the ratio of the average particle size of the inorganic filler to the average particle size of the F particles in the composition is 5 or more.
[0010] The F polymer in the present invention is a polymer containing units (hereinafter also referred to as "TFE units") based on tetrafluoroethylene (hereinafter also referred to as "TFE units"). One type of F polymer may be used, or two or more types may be used. The F polymer may be either heat-fusible or non-heat-fusible, but at least one type of F polymer is preferably heat-fusible. Here, the heat-fusible polymer means a polymer that has a temperature at which the melt flow rate is 1 to 1000 g / 10 min under a load of 49 N. The melting temperature of the thermally meltable F polymer is preferably 180° C. or higher, more preferably 200° C. or higher. The melting temperature of the F polymer is preferably 325° C. or lower, more preferably 320° C. or lower. In this case, the composition is likely to have excellent processability, and a molded product formed from the composition is likely to have excellent heat resistance.
[0011] The glass transition point of the F polymer is preferably 50° C. or higher, more preferably 75° C. or higher. The glass transition point of the F polymer is preferably 150° C. or lower, more preferably 125° C. or lower. The fluorine content of the F polymer is preferably 70% by mass or more, more preferably 72 to 76% by mass. The surface tension of the F polymer is preferably 16 to 26 mN / m. The surface tension of the F polymer can be measured by placing a droplet of a mixture for wetting tension testing (manufactured by Wako Pure Chemical Industries, Ltd.) specified in JIS K 6768 on a flat plate made of the F polymer.
[0012] F polymer is preferably polytetrafluoroethylene (PTFE), a polymer containing TFE units and units based on ethylene (ETFE), a polymer containing TFE units and units based on propylene, a polymer containing TFE units and units based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE units) (PFA), a polymer containing TFE units and units based on hexafluoropropylene (FEP), more preferably PFA and FEP, and even more preferably PFA. These polymers may further contain units based on other comonomers. PAVE is preferably CF2=CFOCF3, CF2=CFOCF2CF3 or CF2=CFOCF2CF2CF3 (hereinafter also referred to as "PPVE"), and more preferably PPVE.
[0013] The F polymer preferably has an oxygen-containing polar group, more preferably has a hydroxyl- or carbonyl-containing group, and even more preferably has a carbonyl-containing group. In this case, the F polymer easily interacts with the inorganic filler, and the composition is easily excellent in dispersibility. In addition, the composition is easily used to obtain a molded product such as a sheet having a low linear expansion coefficient, dielectric constant, and dielectric loss tangent, and excellent heat resistance and thermal conductivity. The hydroxyl-containing group is preferably a group containing an alcoholic hydroxyl group, more preferably -CF2CH2OH or -C(CF3)2OH. The carbonyl group-containing group is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.), a formyl group, a halogenoformyl group, a urethane group (-NHC(O)O-), a carbamoyl group (-C(O)-NH2), a ureido group (-NH-C(O)-NH2), an oxamoyl group (-NH-C(O)-C(O)-NH2) or a carbonate group (-OC(O)O-), and more preferably an acid anhydride residue. When the F polymer has an oxygen-containing polar group, the number of oxygen-containing polar groups in the F polymer is 1×10 6 The number of oxygen-containing polar groups per unit is preferably 50 to 5000, more preferably 100 to 3000. The number of oxygen-containing polar groups in the F polymer can be quantified by the composition of the polymer or the method described in WO 2020 / 145133.
[0014] The oxygen-containing polar group may be contained in a unit based on a monomer in the F polymer, or may be contained in a terminal group of the main chain of the F polymer, the former being preferred. The latter embodiment includes an F polymer having an oxygen-containing polar group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and an F polymer obtained by subjecting an F polymer to plasma treatment or ionizing radiation treatment. The monomer having a carbonyl group-containing group is preferably itaconic anhydride, citraconic anhydride, or 5-norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH"), and more preferably NAH.
[0015] The F polymer is preferably a polymer having a carbonyl group-containing group containing TFE units and PAVE units, more preferably a polymer containing TFE units, PAVE units, and units based on a monomer having a carbonyl group-containing group, and containing these units in this order, 90 to 99 mol%, 0.99 to 9.97 mol%, and 0.01 to 3 mol%, based on all units. Specific examples of such F polymers include the polymers described in WO 2018 / 16644.
[0016] In the present invention, the average particle size (D50) of the F particles is preferably 0.1 μm or more, more preferably 0.3 μm or more. The D50 of the F particles is preferably 25 μm or less, more preferably 10 μm or less, and even more preferably 6 μm or less. The D50 of the F particles is more preferably 0.1 to 6 μm. In this case, the composition is likely to have excellent dispersibility and processability. Furthermore, from the composition, a molded product such as a sheet having a low linear expansion coefficient, dielectric constant, and dielectric loss tangent, and excellent heat resistance and thermal conductivity can be easily obtained. The F particles may be in the form of non-hollow particles or pellets. The specific surface area of F particles is 1 to 50 m 2 / g is preferable, and 1 to 25m 2 / g. The specific surface area of F particles is preferably 6m 2 More preferably, 7m 2 / g or more is more preferable, and 8m 2 The specific surface area of the F particles is particularly preferably 25 m 2 In this case, the above-mentioned mechanism of action is more easily exhibited.
[0017] The F particles are particles containing an F polymer, and preferably consist of an F polymer. The F particles are more preferably particles of a heat-fusible F polymer having an oxygen-containing polar group and a melting temperature of 100 to 320° C. In this case, the above-mentioned mechanism of action is more effectively exerted, and aggregation of the F particles is also easily suppressed. The F particles may contain a resin or an inorganic compound other than the F polymer, may form a core-shell structure with an F polymer as the core and a resin other than the F polymer or an inorganic compound as the shell, or may form a core-shell structure with an F polymer as the shell and a resin other than the F polymer or an inorganic compound as the core. Here, examples of the resin other than the F polymer include aromatic polyester, polyamideimide, polyimide, and maleimide, and examples of the inorganic compound include silica and boron nitride.
[0018] One type of F particle may be used, or two or more types of F particles may be used. The F particles may be mixed with particles of a non-thermofusible tetrafluoroethylene polymer. As the F particles, particles of a heat-fusible F polymer having a melting temperature of 100 to 325°C are preferred, particles of a heat-fusible F polymer having a melting temperature of 180 to 320°C and having an oxygen-containing polar group are more preferred, and as particles of a non-thermofusible tetrafluoroethylene polymer, particles of a non-thermofusible PTFE are preferred. In this case, the aggregation suppression effect of the particles of the heat-fusible F polymer and the retention effect of the fibrillation of the non-thermofusible tetrafluoroethylene polymer are balanced, and the dispersibility of the composition is easily improved. In addition, the electrical properties of the non-thermofusible tetrafluoroethylene polymer are easily expressed to a high degree in the molded product obtained therefrom.
[0019] In the composition, the inorganic filler has a D50 of more than 10 μm, preferably 15 μm or more, more preferably 20 μm or more, and preferably 100 μm or less, more preferably 50 μm or less. The inorganic filler may be an aggregate of primary particles. When the inorganic filler is an aggregate, the average particle size of the aggregate is preferably more than 10 μm. Here, the term "aggregate" means a mass formed by agglomeration of primary particles of a filler having a specific gravity of 2 or more, and the aggregate is more preferably a sintered body obtained by firing.
[0020] The inorganic filler may have any of a spherical, acicular (fibrous) or plate-like shape, but is preferably spherical from the viewpoint of further improving the thermal conductivity of molded products such as sheets obtained from the composition, and of heat dissipation materials such as TIMs containing the composition, as described below. Here, "spherical" may be elliptical, but is preferably substantially spherical. "Substantially spherical" means that, when the filler is observed with a scanning electron microscope (SEM), the ratio of particles having a minor axis to major axis ratio of 0.7 or more accounts for 95% or more. In this case, the composition is likely to have excellent dispersibility and processability. In addition, in a molded product such as a sheet formed from the composition, the inorganic filler is efficiently arranged, and is densely packed while suppressing aggregation, making it easy to form a heat conduction path, and it is easy to obtain a molded product such as a sheet that has excellent mechanical properties, a low linear expansion coefficient, a low dielectric constant and a low dielectric loss tangent, excellent thermal conductivity while maintaining electrical insulation, and reduced surface roughness.
[0021] Examples of the inorganic filler having a specific gravity of 2 or more include nitrides such as aluminum nitride, silicon nitride, and boron nitride; metals such as silicon carbide, silver, and copper; and metal oxides such as aluminum oxide, zinc oxide, titanium oxide, cerium oxide, beryllium oxide, magnesium oxide, nickel oxide, vanadium oxide, copper oxide, iron oxide, and silver oxide. The specific gravity of the inorganic filler is preferably 2.3 or more, and more preferably 3 or more. The upper limit of the specific gravity of the inorganic filler of the inorganic filler is preferably 10. The inorganic filler may be used alone or in combination of two or more kinds. Among these, it is more preferable that the present inorganic filler is a spherical aluminum oxide filler having a D50 of more than 10 μm. Even when the present composition contains an inorganic filler having a large D50 and specific gravity, it is easy to obtain a molded product having excellent electrical properties, low linear expansion, and thermal conductivity.
[0022] The surface of the inorganic filler may be surface-treated. Here, "surface treatment" includes surface treatment using an organic surface treatment agent such as a silane coupling agent, an inorganic surface treatment agent such as an inorganic acid, or a physical operation. However, in a molded product such as a sheet to be described later formed from the composition, the inorganic filler is more densely packed to form paths, and the physical properties of the inorganic filler itself are highly expressed, so that the thermal conductivity of the molded product is further improved. Therefore, it is preferable that the inorganic filler is not surface-treated.
[0023] In the present composition, the ratio of the average particle size (D50) of the present inorganic filler to the D50 of the F particles is preferably 5 or more, more preferably 10 or more. The above ratio is preferably 100 or less, more preferably 50 or less. In such a molded product such as a sheet formed from the present composition, the above-mentioned assumed mechanism is more manifested, and the F particles and the present inorganic filler having different average particle sizes are efficiently arranged, and are densely packed while suppressing their aggregation, making it easy to form a heat conduction path, and it is easy to obtain a molded product such as a sheet having excellent mechanical properties, a low linear expansion coefficient, a low dielectric constant and a low dielectric tangent, excellent thermal conductivity while maintaining electrical insulation, and reduced surface roughness.
[0024] The true density of this inorganic filler is 1-7g / cm 3 is preferred. The bulk density of this inorganic filler is 0.1 to 6.0 g / cm 3 is preferred. The compressive strength of the inorganic filler is preferably 30 to 200 MPa, as measured according to ASTM D 3102-78. The thermal conductivity of the inorganic filler alone is preferably 20 W / m K or more, and more preferably 30 W / m K or more. There is no particular upper limit to the thermal conductivity of the inorganic filler alone, and the higher the better, but in general, it is preferably 3000 W / m K or less, and more preferably 2500 W / m K or less.
[0025] The composition may further contain other fillers other than the inorganic filler, as long as the effect of the present invention is not impaired. Examples of such other fillers include fillers of the above-mentioned metals or their oxides having a D50 of 10 μm or less; silicon compounds having a specific gravity of less than 3, such as silica, quartz powder, wollastonite, talc, and mica; boron nitride; carbon fibers; and carbon allotropes, such as graphite, graphene, and carbon nanotubes.
[0026] Examples of the water-soluble polymer contained in the present composition include acrylic acid polymers, vinyl alcohol polymers, cellulose polymers, polyvinylpyrrolidone, polypyrrole, polythiophene, polyalkylene oxide, and polyethyleneimine. In this specification, the term "water-soluble polymer" refers to a polymer having a solubility in water of 20 g / L or more.
[0027] Examples of acrylic acid-based polymers include polyacrylic acid, salts of polyacrylic acid such as sodium polyacrylate, sodium acrylic acid / maleic acid copolymer, and sodium acrylic acid / sulfonic acid monomer copolymer; polyacrylates such as methyl polyacrylate and ethyl polyacrylate; poly-α-haloacrylate; poly-α-cyanoacrylate; and polyacrylamide. Examples of vinyl alcohol-based polymers include polyvinyl alcohol, polyvinyl acetate, partially acetylated or partially acetalized polyvinyl alcohol, and copolymers of vinyl alcohol, vinyl butyral, and vinyl acetate. Specific examples of vinyl alcohol-based polymers include the "S-LEC (registered trademark) B" series, the "S-LEC (registered trademark) K (KS)" series, and the "S-LEC (registered trademark) SV" series (all manufactured by Sekisui Chemical Co., Ltd.), and the "Mobital (registered trademark)" series (manufactured by Kuraray Co., Ltd.).
[0028] Cellulosic polymers include cellulose ethers such as alkyl celluloses, carboxyalkyl celluloses, hydroxyalkyl celluloses, or hydroxyalkyl alkyl celluloses. Examples of the carboxyalkyl cellulose include carboxymethyl cellulose. Examples of the hydroxyalkyl cellulose include hydroxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose. Examples of the hydroxyalkyl alkyl cellulose include hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose, hydroxyethyl ethyl cellulose, hydroxyethyl ethyl methyl cellulose, etc. These may be used alone or in combination of two or more kinds. As the cellulose-based polymer, carboxyalkyl cellulose, hydroxyalkyl cellulose or hydroxyalkyl alkyl cellulose is preferred, hydroxyalkyl cellulose is more preferred, and hydroxyethyl cellulose is even more preferred. Specific examples of cellulose ethers include the "Sunrose (registered trademark)" series (manufactured by Nippon Paper Industries Co., Ltd.), the "Metolose (registered trademark)" series (manufactured by Shin-Etsu Chemical Co., Ltd.), and "HEC CF Grade" (manufactured by Sumitomo Seika Chemicals Co., Ltd.).
[0029] Among these, from the viewpoints of more effectively expressing the above-mentioned mechanism of action, resulting in excellent dispersibility of the F particles and the inorganic filler in the composition, and of producing a molded product such as a sheet from the composition that is dense and has no uneven distribution of the inorganic filler, has a low linear expansion coefficient, dielectric constant and dielectric tangent, and is excellent in thermal conductivity while maintaining electrical insulation, it is preferable that the water-soluble polymer is at least one selected from the group consisting of acrylic acid-based polymers, vinyl alcohol-based polymers and cellulose-based polymers, and more preferably polyacrylic acid.
[0030] The water-soluble polymer has a weight-average molecular weight (Mw) of 200,000 or more, preferably 300,000 or more, more preferably 500,000 or more, and even more preferably 1,000,000 or more. When the water-soluble polymer has a weight-average molecular weight (Mw) of 200,000 or more, the above-mentioned mechanism of action is realized, the dispersibility of the F particles and the inorganic filler in the composition is excellent, and a molded product such as a sheet formed from the composition has a low linear expansion coefficient, dielectric constant, and dielectric loss tangent, and is excellent in thermal conductivity while maintaining electrical insulation. The Mw of the water-soluble polymer can be measured, for example, by gel permeation chromatography (GPC) using a differential refractive index detector. For example, in the case of an acrylic acid-based polymer, Mw can be measured by GPC analysis using a mixture of methanol / water = 30 / 70 (volume ratio) in which 0.5 mass % sodium acetate is dissolved as an eluent and polyethylene glycol as a standard substance.
[0031] The present composition may further contain other resins different from the F polymer, as long as the effects of the present invention are not impaired. Such other resins may be contained in the present composition as non-hollow particles, or, when the present composition contains a liquid dispersion medium described below, may be dissolved or dispersed in the liquid dispersion medium. Examples of other resins include fluororesins other than F polymers, polyester resins such as liquid crystalline aromatic polyesters, polyimide resins, polyamideimide resins, epoxy resins, maleimide resins, urethane resins, polyphenylene ether resins, polyphenylene oxide resins, and polyphenylene sulfide resins. The other resin is preferably a tetrafluoroethylene polymer other than the F polymer, an aromatic polymer, and more preferably at least one aromatic imide polymer selected from the group consisting of aromatic polyimide, aromatic polyamic acid, aromatic polyamideimide, and a precursor of aromatic polyamideimide. The aromatic polymer is preferably contained in the composition as a varnish dissolved in a liquid dispersion medium.
[0032] The composition may contain other dispersion media in addition to water, as long as the effects of the present invention are not impaired. Such other dispersion media are preferably miscible with water. Examples of other dispersion media include amides such as N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropanamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N,N-diethylformamide, hexamethylphosphoric triamide, and 1,3-dimethyl-2-imidazolidinone; and ketones such as acetone and methyl ethyl ketone.
[0033] From the viewpoint of improving the dispersion stability of the F particles and the inorganic filler, the present composition may further contain a nonionic surfactant in addition to the above-mentioned water-soluble polymer. Examples of the nonionic surfactant include glycol-based surfactants, acetylene-based surfactants, silicone-based surfactants, and fluorine-based surfactants. When the present composition contains a nonionic surfactant, the content of the nonionic surfactant in the present composition is preferably 1 to 15% by volume.
[0034] The present composition may further contain additives such as a thixotropic agent, a viscosity modifier, an antifoaming agent, a dehydrating agent, a plasticizer, a weather resistance agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a whitening agent, a colorant, a conductive agent, a release agent, and a flame retardant.
[0035] The present composition can be obtained by mixing the F particles, the present inorganic filler, the water-soluble polymer, water, and, if necessary, the above-mentioned other resins, other dispersion media, nonionic surfactants, additives, and the like. The composition may be obtained by mixing the F particles, the inorganic filler, the water-soluble polymer, and water all at once, or may be mixed separately in order, or a master batch of these may be prepared in advance and then mixed with the remaining components. There is no particular restriction on the order of mixing, and the mixing method may be either mixing all at once or mixing in several batches.
[0036] For example, it is preferable from the viewpoint of improving dispersibility to preliminarily disperse the F particles and the present inorganic filler in a portion of the water, then add and mix the water-soluble polymer, and add the resulting mixture to the remaining water to obtain the present composition. The water-soluble polymer may be added as a powder or an aqueous solution thereof, or may be added in a state dispersed or dissolved in a liquid defoaming agent or the like. When the above-mentioned other resins, nonionic surfactants, other dispersion media, additives, etc. are further mixed as necessary, they may be mixed when the F particles and water are mixed, or they may be mixed when the mixture is added to water.
[0037] Mixing devices for obtaining the present composition include stirring devices equipped with blades, such as a Henschel mixer, a pressure kneader, a Banbury mixer, and a planetary mixer; grinding devices equipped with media, such as a ball mill, an attritor, a basket mill, a sand mill, a sand grinder, a Dyno Mill, a Dispermat, an SC Mill, a spike mill, and an agitator mill; and dispersing devices equipped with other mechanisms, such as a microfluidizer, a nanomizer, an ultimizer, an ultrasonic homogenizer, a dissolver, a disperser, a high-speed impeller, a thin film swirling high-speed mixer, a planetary stirrer, and a V-type mixer.
[0038] In the present composition, the content of the F particles is preferably 10 to 30% by volume, and the content of the present inorganic filler is preferably 50 to 80% by volume, based on the total amount of the F particles and the present inorganic filler. When the volume concentration is within this range, the composition is likely to have excellent dispersibility. In addition, the composition is likely to produce a molded product such as a sheet that has a low linear expansion coefficient, dielectric constant, and dielectric loss tangent, and in particular has excellent thermal conductivity while maintaining electrical insulation, and has small surface roughness.
[0039] The content of F particles in the composition is preferably 25% by mass or more, more preferably 30% by mass or more, and is preferably 75% by mass or less, more preferably 60% by mass or less.
[0040] In the present composition, the content of the water-soluble polymer relative to the F particles is preferably 0.1 to 1.0% by mass, more preferably 0.2 to 0.8% by mass, and more preferably 0.01 to 1% by mass, more preferably 0.02 to 0.8% by mass, relative to the total mass of the composition.
[0041] The water content in the present composition is preferably 10% by volume or more, more preferably 20% by volume or more, and is preferably 40% by volume or less, more preferably 30% by volume or less.
[0042] The viscosity of the composition is preferably 10 mPa·s or more, more preferably 100 mPa·s or more. The viscosity of the composition is preferably 10,000 mPa·s or less, more preferably 3,000 mPa·s or less. The thixotropy ratio of the present composition is 3 to 15, and from the viewpoints of obtaining good dispersibility and dispersion stability of the F particles and the present inorganic filler in the present composition, and good handleability and processability when forming a molded product such as a sheet from the present dispersion, it is preferably 7 to 13.
[0043] From the viewpoint of improving long-term storage stability, the pH of the present composition is more preferably 8 to 10. The pH of the present composition can be adjusted with a pH adjuster (amine, ammonia, citric acid, etc.) or a pH buffer (tris(hydroxymethyl)aminomethane, ethylenediaminetetraacetic acid, ammonium hydrogen carbonate, ammonium carbonate, ammonium acetate, etc.).
[0044] From this composition, a molded product having a thermal conductivity of 5 W / m·K or more can be easily obtained. The thermal conductivity of such a molded product is preferably 10 to 100 W / m·K. The dielectric constant of the molded article obtained from the composition is preferably 2.4 or less, more preferably 2.0 or less, and more preferably greater than 1.0. The dielectric loss tangent of the molded article is preferably 0.0022 or less, more preferably 0.0020 or less, and more preferably greater than 0.0010.
[0045] The composition can be subjected to a molding method such as extrusion into a sheet to form a sheet-like molded product containing the F polymer and the inorganic filler. The sheet obtained by extrusion may be further cast by press molding, calendar molding, etc. The sheet is preferably further heated to remove the liquid dispersion medium and to bake the F polymer.
[0046] The thickness of the sheet obtained from the composition is preferably 50 μm or more, more preferably 75 μm or more, and even more preferably 100 μm or more, and preferably 1000 μm or less. The suitable ranges of the thermal conductivity, dielectric constant and dielectric dissipation factor of the sheet are the same as those of the above-mentioned molded product. Note that the thermal conductivity of the sheet means the thermal conductivity in the in-plane direction of the sheet. The linear expansion coefficient of the sheet is preferably 100 ppm / ° C. or less, more preferably 80 ppm / ° C. or less. The lower limit of the linear expansion coefficient of the sheet is 30 ppm / ° C. The linear expansion coefficient means a value obtained by measuring the linear expansion coefficient of a test piece in the range of 25° C. or more and 260° C. or less according to the measurement method specified in JIS C 6471:1995.
[0047] The sheet can be laminated on a substrate to form a laminate. Examples of a method for producing a laminate include a method in which the composition is extruded together with the raw material of the substrate using a co-extruder as the extruder, a method in which the composition is extruded onto the substrate, and a method in which the sheet and the substrate are thermally compressed together. Examples of the substrate include metal substrates such as metal foils of copper, nickel, aluminum, titanium, alloys thereof, etc.; films of preferably heat-resistant resins such as polyester, polyimide, polyamide, polyetheramide, polyphenylene sulfide, polyaryl ether ketone, polyamideimide, liquid crystalline polyester, and tetrafluoroethylene-based polymers; prepreg substrates (precursors of fiber-reinforced resin substrates), ceramic substrates such as silicon carbide, aluminum nitride, and silicon nitride; and glass substrates.
[0048] The shape of the substrate may be flat, curved, or uneven, and may be any of a foil, plate, film, and fiber shape. The ten-point average roughness of the surface of the substrate is preferably 0.01 to 0.05 μm. The peel strength between the sheet and the substrate is preferably 10 N / cm or more, more preferably 15 N / cm or more, and is preferably 100 N / cm or less.
[0049] The composition is placed on the surface of a substrate, and a polymer layer containing the F polymer and the inorganic filler is formed, thereby obtaining a laminate having a substrate layer and a polymer layer composed of the substrate. The polymer layer is preferably formed by placing the composition on the surface of the substrate, heating it to remove water and other dispersion media as necessary (hereinafter, water and other dispersion media are collectively referred to as "liquid dispersion media"), and further heating to bake the F polymer. The substrate is separated from the laminate to obtain a sheet containing the F polymer and the inorganic filler. The substrate may be the same as the substrate that can be laminated with the above-mentioned sheet, and the preferred embodiments thereof are also the same.
[0050] Methods for applying the composition include coating, droplet discharging, and immersion, and roll coating, knife coating, bar coating, die coating, and spraying are preferred. The heating for removing the liquid dispersion medium is preferably performed at 100 to 200°C for 0.1 to 30 minutes. In this heating, the liquid dispersion medium does not need to be completely removed, but only needs to be removed to an extent that the layer formed by packing the F particles and the present inorganic filler can maintain a self-supporting film. In addition, when heating, air may be blown to promote the removal of the liquid dispersion medium by air drying.
[0051] The heating for calcining the F polymer is preferably carried out at a temperature equal to or higher than the calcination temperature of the F polymer, more preferably at 360 to 400° C. for 0.1 to 30 minutes. The heating device for each heating may be an oven or a ventilation drying furnace. The heat source in the device may be a contact type heat source (hot air, hot plate, etc.) or a non-contact type heat source (infrared rays, etc.). The heating may be carried out under normal pressure or under reduced pressure. The atmosphere during each heating may be either an air atmosphere or an inert gas atmosphere (helium gas, neon gas, argon gas, nitrogen gas, etc.).
[0052] The polymer layer is formed through the steps of disposing the composition and heating. These steps may be performed once each, or may be repeated two or more times. For example, the composition may be disposed on the surface of a substrate and heated to form a polymer layer, and the composition may be disposed on the surface of the polymer layer and heated to form a second polymer layer. In addition, after the composition is disposed on the surface of a substrate and heated to remove the liquid dispersion medium, the composition may be disposed on the surface of the substrate and heated to form a polymer layer. The composition may be disposed on only one surface of the substrate, or on both surfaces of the substrate, in which case a laminate having a substrate layer and a polymer layer on one surface of the substrate layer is obtained, and in which case a laminate having a substrate layer and polymer layers on both surfaces of the substrate layer is obtained.
[0053] Suitable specific examples of the laminate include a metal-clad laminate having a metal foil and a polymer layer on at least one surface of the metal foil, and a multilayer film having a polyimide film and polymer layers on both surfaces of the polyimide film. The preferred ranges of the thickness, thermal conductivity, dielectric constant, dielectric dissipation factor, linear expansion coefficient, and peel strength between the polymer layer and the substrate layer are the same as the preferred ranges of the thickness, thermal conductivity, dielectric constant, dielectric dissipation factor, linear expansion coefficient, and peel strength between the sheet and the substrate in the sheet obtained from the composition described above.
[0054] The composition is useful as a material for imparting insulating properties, heat resistance, corrosion resistance, chemical resistance, water resistance, impact resistance, and thermal conductivity. Specifically, the composition can be used in printed wiring boards, thermal interface materials, substrates for power modules, coils used in power devices such as motors, vehicle engines, heat exchangers, vials, syringes, ampoules, medical wires, secondary batteries such as lithium ion batteries, primary batteries such as lithium batteries, radical batteries, solar cells, fuel cells, lithium ion capacitors, hybrid capacitors, capacitors (aluminum electrolytic capacitors, tantalum electrolytic capacitors, etc.), electrochromic elements, electrochemical switching elements, electrode binders, electrode separators, and electrodes (positive and negative electrodes). The composition is also useful as an adhesive for bonding parts. Specifically, the composition can be used for bonding ceramic parts, metal parts, electronic parts such as IC chips, resistors, and capacitors on substrates of semiconductor elements and module parts, bonding circuit boards and heat sinks, and bonding LED chips to substrates.
[0055] The present invention also relates to a heat dissipation material containing the composition. A specific example of such a heat dissipation material is a thermal interface material (TIM). The TIM containing the composition has the physical properties of the F polymer and the inorganic filler to a high degree, and is excellent in mechanical properties and heat resistance, has a low linear expansion coefficient, dielectric constant and dielectric dissipation factor, and is particularly excellent in thermal conductivity. In addition, the surface roughness (Rz) is small, and the adhesiveness is excellent. The composition can be particularly suitably used as a TIM for dissipating large amounts of heat generated from electronic components such as computer chips (CPUs), video graphics arrays, servers, game consoles, smartphones, and LED boards, as well as semiconductor modules including power semiconductors used in electric vehicles and inverters and converters in power transmission systems.
[0056] The present invention also relates to a molded product (hereinafter also referred to as "the molded product") that contains the F polymer and the present inorganic filler, has a surface roughness Rz of 25 μm or less, and has a thermal conductivity of 5 W / m K or more. Details of the F polymer, the present inorganic filler, and other optional components in the molded product are the same as those described above in the description of the present composition. The surface roughness Rz of the molded product is preferably 10 μm or less, more preferably 1 μm or less, and is preferably 0.01 μm or more. The thermal conductivity of the molded product is preferably 10 to 100 W / m·K. The molded article is preferably formed from the composition by the above-mentioned method, preferably as a sheet. The thickness of the sheet is preferably 50 μm or more, more preferably 75 μm or more, and even more preferably 100 μm or more. The thickness of the sheet is preferably 1000 μm or less. The suitable ranges of the dielectric constant, dielectric loss tangent, and linear expansion coefficient of the sheet are the same as those described above. Such a sheet can be suitably used as a TIM.
[0057] Molded articles such as sheets and laminates formed from the present composition are useful as antenna parts, printed circuit boards, aircraft parts, automobile parts, sporting goods, food industry products, heat dissipation parts, and the like. Specifically, these include electric wire coating materials (aircraft electric wires, rectangular wires, FFC (Flexible Flat Cable), etc.), enameled wire coating materials used in motors for electric vehicles, etc., power generation coating materials, electrical insulating tapes, insulating tapes for oil drilling, oil transport hoses, hydrogen tanks, materials for printed circuit boards, separation membranes (microfiltration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, gas separation membranes, etc.), electrode binders (for lithium secondary batteries, for fuel cells, etc.), carrier films for fuel cells, tape base films for the semiconductor manufacturing process (dicing tape, pick-up tape, etc.), release films for semiconductor molding, liquid crystal antennas, reflectors, transmission lines, COF (Chip on Fuel) base films for electrostatic chucks for semiconductor manufacturing processes, electrostatic chucks for display manufacturing processes, copy rolls, furniture, automobile dashboards, covers for home appliances, etc., sliding parts (load bearings, yaw bearings, sliding shafts, valves, bearings, bushes, seals, thrust washers, wear rings, pistons, slide switches, gears, cams, belt conveyors, food transport belts, etc.), tension ropes, wear pads, wear strips, tube lamps, test sockets, wafer guides, wear parts for centrifugal pumps, chemical and water supply pumps, tools (shovels, files, drills, saws, etc.), boilers, hoppers, pipes, ovens, baking molds, chutes, racket strings, dies, toilets, container coating materials, heat dissipation boards for mounting power devices, heat dissipation parts for wireless communication devices, transistors, thyristors, rectifiers, transformers, power MOS They are useful as FETs, CPUs, heat dissipation fins, metal heat sinks, blades for wind turbines, wind power generation equipment, and aircraft, housings for personal computers and displays, electronic device materials, interior and exterior parts of automobiles, sealing materials for processing machines and vacuum ovens that perform heat treatment under low oxygen conditions, plasma processing equipment, heat dissipation parts in processing units for sputtering and various dry etching equipment, and electromagnetic wave shielding.
[0058] Molded articles such as sheets and laminates formed from the present composition are useful as electronic substrate materials such as flexible printed wiring boards and rigid printed wiring boards, protective films and heat dissipating substrates, particularly heat dissipating substrates for automobiles. When using a sheet formed from this composition as a TIM, the sheet may be attached directly to the target substrate, or may be attached to the target substrate via an adhesive layer such as a silicone-based adhesive layer.
[0059] Although the present composition, the heat dissipation material containing the present composition, and the present molded article have been described above, the present invention is not limited to the configurations of the above-mentioned embodiments. For example, the present composition may have any other optional configuration in addition to the configurations of the above-mentioned embodiments, or may be replaced with any optional configuration that produces a similar effect. EXAMPLES
[0060] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. 1. Preparation of each ingredient [F polymer particles] F particle 1: containing 97.9 mol%, 0.1 mol%, and 2.0 mol% of TFE units, NAH units, and PPVE units, in that order, and having a carbonyl group-containing group with a main chain carbon number of 1×10 6 Particles of tetrafluoroethylene polymer (F polymer 1, melting temperature: 300°C) with 1000 particles per particle (D50: 2 μm, specific surface area: 7.5 m 2 / g) F particle 2: F polymer 1 particle (D50: 3.8 μm, specific surface area: 5.7 m 2 / g) [Inorganic filler] Alumina 1: Product name "DAM-20" (manufactured by Denka, D50: 25 μm, spherical) [Water-soluble polymer] Water-soluble polymer 1: Polyacrylic acid (weight average molecular weight: 1 million) Water-soluble polymer 2: Polyacrylic acid (weight average molecular weight: 150,000)
[0061] 2. Example of production of liquid composition [Example 1] Water, F particles 1, alumina 1, and water-soluble polymer 1 were added in this order and mixed for 1 minute at 2000 rpm using a planetary centrifugal mixer to obtain liquid composition 1 having an F particle 1 content of 15 mass%, an alumina 1 content of 60 mass%, a water-soluble polymer 1 content of 0.03 mass%, and a water content of 24.97 mass%. The thixotropy ratio of liquid composition 1 was 9.6. [Example 2] A liquid composition 2 having a content of 15 mass% of F particles 2, a content of 60 mass% of alumina 1, a content of 0.03 mass% of water-soluble polymer 1, and a content of 24.97 mass% of water was obtained in the same manner as in Example 1, except that F particles 2 were used instead of F particles 1. The thixotropy ratio of liquid composition 2 was 6.4. [Example 3] A liquid composition 3 was obtained in the same manner as in Example 1, except that water-soluble polymer 2 was used instead of water-soluble polymer 1, and the content of F particles 1 was 15 mass%, the content of alumina 1 was 60 mass%, the content of water-soluble polymer 2 was 0.03 mass%, and the content of water was 24.97 mass%. The thixotropy ratio of liquid composition 3 was 2.4.
[0062] 3. Seat manufacturing and evaluation A wet film was formed on the surface of a copper foil having a thickness of 0.2 μm by applying the liquid composition 1 with an applicator. Then, the glass substrate on which the wet film was formed was passed through a drying oven at 120° C. for 3 minutes and dried to form a dry film. The copper foil substrate with the dry film was cut to 3 cm x 3 cm and heat pressed at 340°C and 10 MPa for 3 minutes to obtain a laminate. The obtained laminate was immersed in an aqueous ferric chloride solution for 2 hours to remove the copper foil, and a sheet 1 with a thickness of 150 μm was obtained. Sheet 3 was produced from Liquid Composition 3 in the same manner as Sheet 1. The cross section of each sheet was observed with a scanning electron microscope (SEM), and it was found that in Sheet 1, no uneven distribution of Alumina 1 was observed, and the cross section was dense and highly uniform. On the other hand, in Sheet 3, uneven distribution of Alumina 1 was observed in the cross section.
[0063] In addition, except for using liquid compositions 1 and 2 that had been stored at 25°C for 3 days, sheet 11 was produced from liquid composition 1 that had been stored at rest, and sheet 21 was produced from liquid composition 2 that had been stored at rest in the same manner as sheet 1 described above. The cross section of each sheet was observed with a scanning electron microscope (SEM), and as a result, no uneven distribution of alumina 1 was observed in sheet 11, and a dense and highly uniform cross section was observed. On the other hand, partial uneven distribution due to aggregation of alumina 1 was observed in the cross section of sheet 21. [Industrial Applicability]
[0064] The composition has excellent dispersibility. Therefore, a sheet formed from the composition is dense and highly uniform, with no uneven distribution of inorganic filler, and exhibits the physical properties of the F polymer and inorganic filler to a high degree, resulting in excellent thermal conductivity, heat resistance, and electrical insulation, making it effective for use as a heat dissipation material.
Claims
1. A liquid composition comprising particles of a tetrafluoroethylene polymer, an inorganic filler having an average particle size of more than 10 μm and a specific gravity of 2 or more, a water-soluble polymer having a weight-average molecular weight of 200,000 or more, and water, and having a thixotropy ratio of 3 to 15.
2. 2. The liquid composition according to claim 1, wherein a ratio of an average particle size of the inorganic filler to an average particle size of the tetrafluoroethylene-based polymer particles is 5 or more.
3. 2. The liquid composition according to claim 1, wherein the average particle size of the tetrafluoroethylene polymer particles is 0.1 to 25 μm.
4. The specific surface area of the tetrafluoroethylene polymer particles is 6 m 2 The liquid composition of claim 1 , wherein the viscosity is greater than 100 μm / g.
5. The liquid composition according to claim 1 , wherein the tetrafluoroethylene-based polymer is a heat-fusible tetrafluoroethylene-based polymer having an oxygen-containing polar group.
6. The liquid composition according to claim 1 , wherein the inorganic filler has an average particle size of more than 10 μm and not more than 100 μm.
7. The liquid composition according to claim 1 , wherein the inorganic filler is a metal or a metal oxide.
8. 2. The liquid composition according to claim 1, wherein the content of the tetrafluoroethylene-based polymer particles is 10 to 30 volume % and the content of the inorganic filler is 50 to 80 volume % relative to the total amount of the tetrafluoroethylene-based polymer particles and the inorganic filler.
9. The liquid composition according to claim 1 , wherein the water-soluble polymer has a weight average molecular weight of 1,000,000 or more.
10. The liquid composition according to claim 1 , wherein the water-soluble polymer is at least one selected from the group consisting of acrylic acid-based polymers, vinyl alcohol-based polymers, and cellulose-based polymers.
11. 2. The liquid composition according to claim 1, wherein the content of the water-soluble polymer relative to the amount of the tetrafluoroethylene-based polymer particles is 0.1 to 1.0% by mass.
12. A heat dissipating material comprising the liquid composition according to any one of claims 1 to 11.
13. A method for producing a molded product, comprising extruding the liquid composition according to any one of claims 1 to 11 or disposing it on a surface of a substrate to obtain a molded product containing the tetrafluoroethylene-based polymer and the inorganic filler.
14. A molded article comprising particles of a tetrafluoroethylene-based polymer and an inorganic filler having an average particle size of more than 10 μm and a specific gravity of 3 or more, the molded article having a surface roughness Rz of 25 μm or less and a thermal conductivity of 5 W / m·K or more.
15. The molded article according to claim 14, having a thickness of 100 μm or more.
Citation Information
Patent Citations
Fluorine-based resin-aluminum oxide mixed dispersion and method for producing the same
JP2017110220A